2013
DOI: 10.1038/jid.2012.486
|View full text |Cite
|
Sign up to set email alerts
|

Xiamenmycin Attenuates Hypertrophic Scars by Suppressing Local Inflammation and the Effects of Mechanical Stress

Abstract: Hypertrophic scarring is a common disease affecting millions of people around the world, but there are currently no satisfactory drugs to treat the disease. Exaggerated inflammation and mechanical stress have been shown to be two main mechanisms of excessive fibrotic diseases. Here we found that a benzopyran natural product, xiamenmycin, could significantly attenuate hypertrophic scar formation in a mechanical stretch-induced mouse model. The compound suppressed local inflammation by reducing CD4+ lymphocyte a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 49 publications
(64 reference statements)
1
45
0
1
Order By: Relevance
“…The results of this observational study suggest that a reduced early inflammatory response is associated with HTS formation. This might be interpreted as being in conflict with the current conception that HTS is related to excessive inflammation . However, previous research of our group also demonstrated signs of decreased inflammation in HTS formation, which supports the findings of the present study …”
Section: Discussionsupporting
confidence: 67%
“…The results of this observational study suggest that a reduced early inflammatory response is associated with HTS formation. This might be interpreted as being in conflict with the current conception that HTS is related to excessive inflammation . However, previous research of our group also demonstrated signs of decreased inflammation in HTS formation, which supports the findings of the present study …”
Section: Discussionsupporting
confidence: 67%
“…Thus, contraction can be regarded as a key pathogenic step in PVR. Cells cultivated in the three-dimensional collagen gel system recapitulated similar morphological changes as observed in vivo 343536. Collagen gel contraction has been used as a model of wound healing process mediated by various cell types, particularly in transdifferentiated RPE cells373839.…”
Section: Discussionmentioning
confidence: 62%
“…Excessive development of scar‐forming fibroblasts is at the root of pathological scar formation . However, therapeutic options for excessive scarring are limited, and seldom have they been proven to be effective .…”
Section: Discussionmentioning
confidence: 99%